Are policy makers aware of the climate security nexus? Mapping climate security policy narratives in Nigeria - Carneiro, Bia; Resce, Giuliano; Läderach, Peter R.D.; Pacillo, Grazia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This factsheet answers if policy makers are aware of the climate security nexus, using social media analysis. The results show a disassociation between climate, socioeconomic insecurities, and conflict in the public communications of policy makers.